Metabolic syndrome and risk of esophageal adenocarcinoma in elderly patients in the United States: An analysis of SEER‐Medicare data. Issue 4 (8th November 2016) - Drahos, Jennifer; Ricker, Winnie; Pfeiffer, Ruth M.; Cook, Michael B.
Abstract : BACKGROUND: Metabolic syndrome (MetS) is associated with cancer risk and increases the risk of Barrett esophagus, which is the precursor lesion of esophageal adenocarcinoma (EA), primarily in the absence of gastroesophageal reflux disease (GERD). However, to the authors' knowledge, little is known regarding whether MetS is associated with the risk of EA. METHODS: Using the Surveillance, Epidemiology, and End Results (SEER)‐Medicare‐linked database, the authors evaluated whether MetS was associated with EA. A total of 3167 cases of EA were compared with individually matched population controls (5:1); a subset of 575 EA cases were able to be individually matched with 575 Barrett esophagus controls. MetS was defined using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) codes in the period 1 to 3 years before the diagnosis of EA or control selection. Unconditional logistic regression was used to estimate adjusted odds ratios and 95% confidence intervals. Potential effect modification by GERD symptoms and sex was examined in stratified models. RESULTS: EA was found to be significantly associated with MetS (odds ratio, 1.16; 95% confidence interval, 1.06‐1.26) compared with population controls. In males, the association was restricted to those individuals without prior GERD; however, in females, MetS was found to be associated with EA regardless of GERD status. Effect modification by sex was observed ( P for interaction = .01). MetS was not found to be associated with EA risk when compared with Barrett esophagus controls. CONCLUSIONS: In this older population, MetS was found to be associated with an increased risk of EA in males without GERD and females regardless of GERD status. Given the lack of an association when compared with Barrett esophagus controls, MetS may impact EA risk by primarily increasing the risk of the precursor lesion, Barrett esophagus. Cancer 2017;123:657–665. © 2016 American Cancer Society . Abstract : Metabolic syndrome appears to be associated with an increased risk of esophageal adenocarcinoma in males without gastroesophageal reflux disease and females regardless of gastroesophageal reflux disease status in the Surveillance, Epidemiology, and End Results‐Medicare‐linked database. Metabolic syndrome may impact the risk of esophageal adenocarcinoma primarily by increasing the risk of the precursor lesion Barrett esophagus.